The Effectiveness of a Psychological Program for Enhancing Psychological Resilience Among Abused Women - Mousa, Shireen Safar; Omar, Jehan Hussein (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
This study aims to test the effectiveness of a psychological program in enhancing psychological resilience among abused women in the Domiz refugee camp in Kurdistan Region of Iraq. The research employed an experimental one-group design (pre-test/post-test) with a purposive sample of abused women. Results showed that participants before the program implementation suffered from low levels of psychological resilience compared to the hypothetical mean of the scale, reflecting the impact of violence, psychological trauma, and refugee conditions on their ability to adapt. After implementing the psychological program, the results demonstrated a significant statistical improvement in psychological resilience levels among the sample members, confirming the effectiveness of the applied psychological program. The findings also indicated a significant decrease in cortisol levels, suggesting improved physiological indicators related to psychological stress. These results emphasize the importance of structured psychological interventions based on scientific foundations in helping abused women recover from the effects of violence and trauma, and highlight the necessity of generalizing such programs in refugee camps and institutions caring for abused women, considering them part of preventive and therapeutic strategies to address psychological and social challenges.